Evaluation of the antiproliferative potential of Açaí (Euterpe oleracea Mart.) isolated or in association to 5-fluorouracil against HeLa cells - Djenifer Ulrich; Kolinski Machado, Amanda; Marcia dos Santos Mota , Kennya; Rorato Sagrillo, Michele; Kolinski Machado, Alencar; valente, diulie (Disciplinarum Scientia | Saúde, 2025)
Cancer constitutes a major problem for society, the occurrence of this disease is associated with the aging of the population, as well as the increased prevalence of risk factors. Cervical cancer is the third most common type of cancer in the women, and fourth leading cause of cancer-related deaths among women in Brazil. Around 60% of the currently used antineoplastic drugs were discovered from natural products, Euterpe oleracea Mart. popularly known as açaí, has been the subject of many studies in recent years, due to its high consumption, and its rich content of phytochemicals, particularly polyphenols, which have shown antiproliferative and pro-apoptotic effects in tumor cells, as well as tumor suppression, prevention adipogenesis, reduction of oxidative stress, and strong anti-inflammatory activity. This study aimed to evaluate the antiproliferative activity of the fruit, using its hydroalcoholic extract either alone, or combined with the chemotherapeutic drug 5-Fluorouracil. HeLa cells were cultured in a CO2 incubator and treated with different concentrations of the extract (0.01-1000 μg/mL). The cytotoxicity of the same was evaluated by the cell viability assay using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide and evaluation of cellular metabolism was performed by the total rate of nitric oxide production. The results showed potential for the reduction of cell proliferation, especially at the concentration of 1 μg /mL, and for cell metabolism, the cells exhibited similar rates to the negative control at the lowest concentrations.